Anti-TNF therapy of ankylosing spondylitis in clinical practice. Results from the Czech national registry ATTRA - Pavelka, K; Forejtová, S; Stolfa, J; Chroust, K; Buresová, L; Mann, H; Vencovský, J (Clinical and experimental rheumatology, 2009)
OBJECTIVES: To estimate efficacy, safety and adherence to therapy of ankylosing spondlitis (AS) patients included in the Czech National Registry ATTRA, and to look for predictive factors for therapy discontinuation. METHODS: Patients were included according to the guidelines of the Czech Society for Rheumatology, which involve failure of previous therapy, BASDAI >4, and CRP >10 mg/l. Only patients with anti-TNF administered for the first time were analysed. Adherence to therapy was evaluated using Kaplan-Meier analysis and results were presented as cumulative survival. Comparison with data on patients with rheumatoid arthritis (RA) followed in the same registry was made. RESULTS: 310 of AS patients who had reached at least 1 year as well as those who discontinued the treatment before this time point were analysed. Drug survival was longer in patients with AS than in those with RA: 84% vs. 78% and 72% vs. 49% after 1 and 3 years of treatment. Significant risk factors for treatment discontinuation were female gender (RR 2.22, p=0.001) and CRP (RR 1.33, p=0.025). The proportion of patients with BASDAI <4 during the treatment period was higher in the etanercept group than in the infliximab group (p<0.001). The number of patients fully employed increased in the whole group from 48% to 63% after 1 year of treatment. CONCLUSION: Follow-up of patients with AS in the national registry shows that it is an effective and safe way of treatment with longer adherence to anti-TNF therapy in comparison with RA patients.
Keywords: Registries; náklady na léky; ankylózující spondylitida; Humans; registrace; Arthritis, Rheumatoid; Drug Costs; antirevmatika; Cost of Illness; Antibodies, Monoclonal; Female; Patient Compliance; výsledek terapie; lidé; Regression Analysis; časové faktory; TNF-alfa; revmatoidní artritida; osobní újma zaviněná nemocí; ženské pohlaví; Kaplanův-Meierův odhad; stupeň závažnosti nemoci; Male; Treatment Outcome; Spondylitis, Ankylosing; Czech Republic; monoklonální protilátky; Severity of Illness Index; Tumor Necrosis Factor-alpha; Kaplan-Meier Estimate; Česká republika; mužské pohlaví; adherence pacienta; Time Factors; Antirheumatic Agents; regresní analýza